2016
DOI: 10.7763/ijiet.2016.v6.709
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Programming Experience in ICT Students’ Learning Motivation and Academic Achievement

Abstract: Abstract-There is a high demand for qualified Information and Communication Technology (ICT) practitioners in the European labor market. However, a high dropout rate in higher education among ICT students is a big problem. One reason why students drop out is low study motivation, which in turn can influence the learning outcomes. Prior experience, such as learning ICT at the general education level and working in ICT field may influence their study motivation and learning outcomes at the higher education level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 24 publications
(40 reference statements)
2
25
1
3
Order By: Relevance
“…It was also found that those IT students who had previous experience in programming did better in their higher education studies than those with no past programming experience [33]. Previous programming experience gave the students an advantage in the first and second semester -those…”
Section: Studying It and Academic Performancementioning
confidence: 77%
“…It was also found that those IT students who had previous experience in programming did better in their higher education studies than those with no past programming experience [33]. Previous programming experience gave the students an advantage in the first and second semester -those…”
Section: Studying It and Academic Performancementioning
confidence: 77%
“…Prior programming experience has been found to be useful for ICT students (Hagan & Markham, 2000;Kori et al, 2016), but the students who had learned ICT at a general education level did not find the knowledge to be useful at university. Students also had different goals for studying ICT at university, but only a few had sufficient information about the curriculum.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…On leitud, et varasema programmeerimiskogemusega üliõpilased saavutavad paremaid õpitulemusi (Hagan & Markham, 2000) ja hindavad õpinguid kõrgkoolis lihtsamaks kui varasema programmeerimiskogemuseta üliõpilased (Kori, Pedaste, Leijen, & Tõnisson, 2016). Seega võivad IKT-õpingud keeruliste programmeerimise ja matemaatika õppeainete tõttu pooleli jätta just need üliõpilased, kellel puuduvad programmeerimiskogemused.…”
Section: Ikt Erialade Spetsiifikaunclassified
“…Moreover, studies have also looked at the value of using different programming languages, but overall it is important for students not to confuse the learning of programming with the learning of a programming language (Cazzola and Olivares 2016). In terms of motivation previous experience and interest have been shown to play a very important factor in engagement and achievement (Ashok Kumar et al 2017;Kori et al 2016). For this reason, there have been many attempts to build upon such findings by implementing strategies that showcase to non-computer science majors that programming is not a special talent, but something everyone can do with the right motivation and practice.…”
Section: First Year Programming Coursesmentioning
confidence: 99%